"3M": Migraine, Microbiota and Melatonin. (June 2019) - Boutrid, N.; Rahmoune, H.
Abstract: We read with deep interest the recent article published on "Medical Hypotheses" about migraine and associated gastrointestinal disorders. Beyond the exhaustive pathophysiological explanations, we would address some relevant points to the role of melatonin as well as the high potential of intestinal microbiota in such conditions.